Digest: Within and between sex covariances can enhance the response to climatic selection. (19th December 2019) - Sztepanacz, Jacqueline L.
Abstract: Do genetic covariances promote or impede rapid adaptation to changing environments? Hangartner et al. found that genetic covariances among traits and between sexes aligned with the inferred direction of selection along a latitudinal cline, suggesting that genetic covariances can augment the evolutionary response to climatic selection.